Identifying the Websites that Maintain Operational Standards through Obligation Links to Website-Standards Approval Body - et. al., Srihari Rao Nidamanuru, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Website is a very interesting phenomenon on the Internet. It attracts almost everyone as it can be viewed and used just by sitting in one place and exploring the many facets of information. That is the reason every institute whether for profit or non-profit establishes an online channel in the form of a website to manifest its significance both online and offline. Unfortunately, today the very purpose of the www on the Internet is abused by so many cybercriminals and their accomplices. By our many observations and website browsing and navigation experiences, we felt the need to assess any website and to approve/disapprove the special identification given to any website that meets certain operational standards. In this paper, we proposed a policy and a method to be adopted by Website-Standards Approval Body (WSAB) in order to assess the websites for approval/disapproval. This method is based on improving a parameter called Value-Identifier (VI) that is computed on the basis of certain important factors which are applied onto any website. We followed an empirical approach to assess the effectiveness of our method by following the operational standards to a set of 4 websites known to us. The larger and sufficient VI value is demonstrated by two of these operational-standard qualifying websites against the other two operational-standards non-qualifying websites.